Recent Progress in Synaptic Devices Paving the Way toward an Artificial Cogni‐Retina for Bionic and Machine Vision. (8th May 2019) - Berco, Dan; Shenp Ang, Diing
Abstract : The state‐of‐the‐art conception of a bionic/robotic eye is a somewhat bulky multipart system comprising a video camera connected to a processing unit that in turn communicates data through a wireless transmitter to either an in vivo retinal implant or a computer system. An artificial cogni‐retina is a millimeter‐scale, intelligent apparatus designed as a replacement for these systems, while executing simple image processing tasks. As a bionic limb, it can connect directly to the optic nerve and perform rudimentary cognitive functions such as perceiving, learning, remembering, and classifying elementary visual data. This theoretical system presents a quantum leap in terms of size, power consumption, and speed to both prosthetic human eyes and robotic vision in artificial intelligence‐based platforms such as autonomous vehicles. Recently, an increasing number of publications have used interesting materials in artificial synaptic devices that drive this idea closer toward becoming a real‐world application. Such devices may form a basis for hardware‐based deep learning artificial neural networks that can potentially execute image processing tasks within a single clock cycle compared to software algorithms running on conventional von Neumann machines that require millions of cycles to perform image sensor interfacing, memory fetch operations, and data path propagation. Abstract : An artificial cogni‐retina (thinking eye) has the potential to perform image recognition tasks within sub‐nanosecond delays. It is based on an artificial neural network that can be used to capture an image as a bitwise imprint of visual information. Image processing is performed by parallel feed‐forward propagation of the computation through the network.